The Power of Visual Communication Design: A Visual Study of the 2000 United States Presidential Election Ballot Layout and the 2015 Miss Universe Winner Announcement Card Layout - Gozin Najah Rusyada; Christofer Satria; Sasih Gunalan (Jurnal Ilmu Sosial dan Humaniora, 2023)
The 2000 United States presidential election and the mistake in announcing the winner of the 2015 Miss Universe beauty pageant contest are controversial events in the world that are thought to have occurred due to poor layout designs. This study used a qualitative approach employing a descriptive method with the researcher as the main instrument. The data in this study are in the form of sentence description obtained from the results of the layout study analyzed using the theory of it works, it organizes, and it attracts. The research subjects are the ballot layout design for the 2000 United States presidential election and the 2015 Miss Universe winner announcement card layout. The results showed that the ballot layout design for the 2000 United States presidential election and the 2015 Miss Universe winner announcement card layout design, based on the theory of it works, it organizes, and it attracts, do not meet the basic categories of a good layout.